2002
DOI: 10.1136/adc.87.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Two administration methods for inhaled salbutamol in intubated patients

Abstract: Aims: To compare serum concentrations and effects on respiratory mechanics and haemodynamics of salbutamol administered by small volume nebuliser (SVN) and metered dose inhaler (MDI) plus spacer. Methods: Blinded, randomised, crossover study in 12 intubated infants and children (mean age 17.8 months) receiving inhaled salbutamol therapy. Subjects received salbutamol as 0.15 mg/kg by SVN and four puffs (400 µg) by MDI plus spacer at a four hour interval in random order. Passive respiratory mechanics were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…3). 55 Garner et al 65 reported similar clinical effects and albuterol concentrations in ventilated subjects receiving albuterol therapy via pMDI/spacer (between Y-piece and ETT) and a jet nebulizer placed in the inspiratory limb (10 -20 cm before the Y-piece).…”
Section: Delivery Device Selection For Mechanically Ventilated Pediatmentioning
confidence: 89%
“…3). 55 Garner et al 65 reported similar clinical effects and albuterol concentrations in ventilated subjects receiving albuterol therapy via pMDI/spacer (between Y-piece and ETT) and a jet nebulizer placed in the inspiratory limb (10 -20 cm before the Y-piece).…”
Section: Delivery Device Selection For Mechanically Ventilated Pediatmentioning
confidence: 89%
“…Other factors that may modify particle lung deposition when using pMDI aerosol in ventilated humans are the ventilator mode, settings, and circuit [ 47 ], and synchronization of pMDI application with breaths, among other factors [ 48 ]. In addition, the therapeutic response may be influenced by the patient’s airway anatomy and disease severity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wildhaber 27 mostra que o inalador dosimetrado acoplado a dois tipos de espaçadores disponibiliza para inalação uma maior quantidade de partículas (40,2% e 40,7% das partículas geradas) que o nebulizador (25,3%). Os estudos revistos (Tabela 6), que compararam nebulizador com aerossol dosimetrado acoplado a espaçador 14,[18][19][20][21][22][23] , também utilizaram doses diferentes nos dois sistemas inalatórios (4 a 37 vezes maior com o nebulizador, conforme o estudo). Um trabalho em modelo de pulmão neonatal em ventilação mecânica 23 mostrou a equivalência entre 100 µg (através de aerossol dosimetrado com espaçador) e 2.500 a 3.700 µg (através de nebulizador), medindo a quantidade de droga depositada nas vias aéreas inferiores centrais.…”
Section: Discussionunclassified